Kinetics of CO2 adsorption on ball-type dicopper phthalocyanine thin film - Altindal, Ahmet; Kurt, Ozgur; Sengul, Abdurrahman; Bekaroglu, Ozer (ELSEVIER SCIENCE SA, 2014)
Adsorption kinetics of CO2 on ball-type dicopper phthalocyanine thin film had been studied. The experimental data were analysed using four adsorption kinetic models; the pseudo first- and second-order equations, Ritchie's equation and the Elovich equation to determine the best fit equation for the adsorption of CO2 gas onto dicopper phthalocyanine thin film. The rate constants, equilibrium capacities and related correlation coefficients for each kinetic model were calculated and discussed. Results show that the linear regression analysis with respect to Ho's pseudo second order rate equation generates a straight line that best fit to the data of adsorption of CO2 on Pc film. It, unexpectedly, does not fit Elovich's or Ritchie's equation which are widely used in describing the adsorption of gaseous particles on solid systems. The variation of current in ball-type CuPc thin film as a function of temperature at constant bias voltage were also studied in the presence of CO2, SO2 and CO gases. While exposure to SO2 and CO have no considerable influence on the electrical conductivity of compound 4, the conductivity of the film strongly depend on the presence of the CO2 gas. The results indicated that the film of compound 4 has potential as a sensitive coating for the monitoring of CO2 gas even at room temperature. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthlocyanine; CO2 sensing; Sensitivity; Adsorption kinetics; Sensing mechanism; GAS-SENSING PROPERTIES; HETERO-DINUCLEAR PHTHALOCYANINES; NITROGEN-DIOXIDE EXPOSURE; ELOVICH EQUATION; ZINC-PHTHALOCYANINE; METAL-FREE; NO2; SORPTION; COPPER; SENSORS; Chemistry; Electrochemistry; Instruments & Instrumentation